FRAMING CONSTRUCTION OF HABIB RIZIEQ CASE NEWS IN TEMPO MAGAZINE IN 2017 - Dwijayanti, Risqi Inayah (Jurnal Ilmiah Universitas Satya Negara Indonesia, 2024)
This research discusses the framing of news done by Tempo magazine on 23 - 29 January 2017 issue in Habib Riziek case report which utilize positioning of religion figure in mass media as a tool of selling (commodity) to be able to invite public opinion and sense of community sentiment towards the character. The analytical methods used were Zhongdang Pan and Gerald M. Kosicki. In analyzing, this method uses four structures that consist of, Structure Syntax is how journalists arrange events, Structure Scripts is how journalists tell or tell events into news form, Thematic Structure is how journalists express the views of events into propositions, sentences or relations Between sentences that make up the text as a whole, and the Rhetorical Structure that is the issue of Rizieq's interest in building his name that was vacuum among the wider community and in the mass media.